KAJIAN TIPOLOGI POTENSIAL STRUKTUR DEMOGRAFI INDONESIA TERHADAP TIPOLOGI DAUR HIDUP PRODUK DAN BIDANG USAHA KOPERASI INDONESIA - Sumantri, Bambang Agus (LIPI, 2018)
The phenomenon of cooperatives in Indonesia Per quarter I-2017, based on data Kemenkop SMEs, the number of cooperatives throughout Indonesia recorded 212 thousand units, but the active only 150 thousand units. This research method using qualitative approach, using literature review. The literature review is to analyze the relationship pattern and typology form. Where the pattern of relationship and form is divided into 3 typologies. First, the potential of Indonesias demographic structure. Secondly, the typology of the life cycle period of Indonesian cooperative products. Third, the typology of Indonesian cooperative business. The life cycle of Indonesian cooperative organization product management is based on the demographic characteristics of generations X, Y, and Z in Indonesia, as well as the period after Act No. 25 of 1992 on Cooperatives and Law No. 17 of 2012. And Draft of Cooperative Law. The subject of this research is Indonesian cooperative that exist until December 2017. The object of research is product life cycle management. Data collection is derived from other secondary sources (web sites, books, laws, other documents) as per this studys study. The results of product life cycle management research on Indonesian cooperative organization are: The potential of Indonesias demographic structure consists of 3 generations, namely generation X (boomer generation), generation Y (millennial generation) and generation Z. Product life cycle management, can be classified five, namely: traditional, pre modern, modern, digital, on-line. 9 concepts of typology of business, namely: Cooperative Business Sector Agriculture, Livestock and Agribusiness (Agriculture Farm); Cooperative Business Sector of Mining (Mining); Cooperative in the Business of Handicrafts and Manufacturing (Manufacturing); Cooperative of Building and Construction Business Sector (Construction); Cooperative Business Sector Marketing and Trade (Trade); Financial and Insurance Service Business Cooperation (Finacial Assurance Service); Cooperative Field of Personal Services; Cooperative Field of Technology, Information and Public Services (Public Sevice); Cooperative Field Tourism services (Tourism).